Controlled drug delivery by means of drug :i onic polysaccharide interactions - Morton-Holmes, Danya Frances (1993)
The aim of the project was to investigate the potential of ionic polysaccharide/drug complexes as controlled release drug delivery systems. Two highly purified alginates from Laminaria hyperborea and Ascophyllum nodosum were characterised in terms of molecular weight, polydispersity and M:G ratio using gel permeation chromatography (GPC), low-speed sedimentation in the analytical ultracentrifuge and GPC combined with multi-angle laser light-scattering. Viscometric and nephelometric studies provided evidence that, above certain concentrations of propranolol, there was an interaction between propranolol and alginate in deionised water resulting in the formation of an insoluble complex, which dissociated in the presence of counter-ions, for example, sodium chloride. Binding studies were undertaken using equilibrium dialysis in order to quantify this interaction in the presence and absence of sodium chloride. These indicated that there was a one-to-one stoichiometric relationship between propranolol and the carboxyl group on each uronic acid reSidue of the alginate and that negative co-operativity was occurring, such that the binding of one propranolol molecule to the alginate made it more difficult for subsequent propranolol molecules to bind. The possible in-vacuo three-dimensional structure of the molecular complex was modelled using computational molecular modelling techniques. A freeze-dried complex of propranolol and alginate was prepared and characterised. In vitro investigations indicated that drug release from the complex (formulated as a suspension in deionised water or in isotonic glycerol solution) was delayed compared with release from a propranolol solution. The release of propranolol from the propranolol/ alginate complex was assessed in vivo using the anaesthetised rat as an animal model for nasal delivery. It was found that the rate of absorption of propranolol from the complex was much slower and was sustained over a greater period of time, compared with absorption from a propranolol solution. In addition, the bioavailability of the drug from the complex was comparable to that of the solution and to that of an intravenous dose carried out in rats by other workers (Hussain et al 1980b).